Swim encounters with killer whales (Orcinus orca) off Northern Norway: interactive behaviours directed towards human divers and snorkellers obtained from opportunistic underwater video recordings. Issue 2 (4th May 2017) - Pagel, Chantal Denise; Scheer, Michael; Lück, Michael
ABSTRACT: Encounters of humans with wild animals should be investigated before commercial operations will be established. This study describes interactive behaviours of wild and unhabituated Norwegian killer whales ( Orcinus orca ) during close encounters with video-filming human divers and snorkellers. Swimmers followed a code-of-conduct to minimise disturbance. Interactive behaviours initiated by cetaceans and shown in close proximity to human swimmers can be described using an ethogram. Such a behavioural catalogue provides baseline data for managing in-water encounters. This study uses opportunistic underwater video recordings. Videos were scanned for interactive behaviours and their relative occurrence was measured. In total, eight interactive behaviours were found that are considered to be exclusively affiliative in nature. The most frequent behaviours were 'calling' [ M  = 0.74] and 'eye contact' [ M  = 0.67]. No aggressive behaviours were found. The present results facilitate the first description of interspecific killer whale behaviours occurring during in-water encounters with snorkellers and divers which is essential to manage interactions properly in the future.